Single Stage Bilateral Total Knee Arthroplasty -Patient Safety and Functional Outcome - Thapa, Sunil Singh; Neupane, Prayoush; Arjun, Lamichhane; Mahara, Dipak Prakash (Nepal Orthopaedic Association Journal, 2019)
INTRODUCTION: Knee Osteoarthritis is a common disorder of knee joint in patient over 60 years age. Total knee arthroplasty provides pain relief and improvement in function in end stage osteoarthritis. Controversy exist between single stage versus staged total knee arthroplasty, proponent's claims reduced cost, single anesthesia, symmetric rehabilitation and reduced overall hospital stay as advantage of single stage surgery while other believes increased risk of mortality and morbidity compared to staged bilateral total knee replacement. In this study we looked for the patient safety and functional outcome of single stage bilateral total knee replacement in our center.METHODOLOGY: All single stage bilateral total knee replacement done in sports and arthroplasty unit of department of orthopedics in Tribhuvan University Teaching Hospital between May 2016 to November 2017 were prospectively followed for one year. Immediate and early postoperative complications were recorded and functional outcome at one year was analyzed using hospital for special surgery knee score.RESULTS: Mean age of patients was 68.02±6.87 years, of them 24 were female and 7 were male. Mean drop in hemoglobin postoperatively was 2.47±1.33 gm/dl; of them 16 %( 5 cases) required blood transfusion. Functional outcome at 1 year follow was excellent in 38.7 %( 12 cases) and good in 61.3 %( 19 cases).CONCLUSION: Single stage bilateral total knee arthroplasty has good functional outcome without significant increase in morbidity and mortality at one year follow-up.